POSITIONING IN BLUETOOTH AND UWB NETWORKS - Campos, Rafael Saraiva (Cadernos do IME - Série Informática, 2017)
This article brings a comprehensive tutorial on radio-frequency (RF) positioning in Bluetooth and Ultra-Wideband (UWB) Wireless Personal Area Networks (WPANs), carrying out an extensive literature review, providing the reader an overview of Bluetooth and UWB RF positioning state-of-the-art. It also delves into some key issues, such as multi-lateration based solutions using received signal strength and time-of-arrival, multi-slope linear regression, RF fingerprinting and the use of clustering techniques to improve its localization accuracy, the interrelation between Bluetooth versions improvements and new positioning capabilities, as well as localization prospects in future UWB networks.